From Collective Identity to Counter-Hegemony - Belolon, Handrianus Koli (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
In mass media, such as films, the Papuan region and people are still regarded as “the other